2017
DOI: 10.1038/s41598-017-11915-5
|View full text |Cite
|
Sign up to set email alerts
|

Syk-dependent tyrosine phosphorylation of 3BP2 is required for optimal FcRγ-mediated phagocytosis and chemokine expression in U937 cells

Abstract: The adaptor protein c-Abl SH3 domain binding protein-2 (3BP2) is tyrosine phosphorylated by Syk in response to cross-linking of antigen receptors, which in turn activates various immune responses. Recently, a study using the mouse model of cherubism, a dominant inherited disorder caused by mutations in the gene encoding 3BP2, showed that 3BP2 is involved in the regulation of phagocytosis mediated by Fc receptor for IgG (FcγR) in macrophages. However, the molecular mechanisms underlying 3BP2-mediated regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…SH3BP2 interacts with several proteins including spleen tyrosine kinase (SYK), 14-3-3, VAV, LYN, SHP-1, and PLCγ1/2, indicating that SH3BP2 is involved in a variety of cellular functions. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Gainof-function mutations in SH3BP2 are responsible for a human craniofacial disorder, cherubism (OMIM#118400). (32) Analysis of a knock-in mouse model for cherubism revealed that a cherubism mutation increases osteoclastogenesis induced by RANKL and TNF-α and enhances macrophage responsiveness to pathogen-associated molecular patterns (PAMPs) via TLRs.…”
mentioning
confidence: 99%
“…SH3BP2 interacts with several proteins including spleen tyrosine kinase (SYK), 14-3-3, VAV, LYN, SHP-1, and PLCγ1/2, indicating that SH3BP2 is involved in a variety of cellular functions. (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Gainof-function mutations in SH3BP2 are responsible for a human craniofacial disorder, cherubism (OMIM#118400). (32) Analysis of a knock-in mouse model for cherubism revealed that a cherubism mutation increases osteoclastogenesis induced by RANKL and TNF-α and enhances macrophage responsiveness to pathogen-associated molecular patterns (PAMPs) via TLRs.…”
mentioning
confidence: 99%
“…As described in the previous section, SH3BP2 is ubiquitously expressed in various immune cells, such as macrophages and lymphocytes. Previous studies revealed that excessive amounts of SH3BP2 in macrophages enhance the production of inflammatory cytokines [52,65,68] and increase phagocytic activities [88,89]. Additionally, a deficiency in SH3BP2 impairs B-cell functions [90,91].…”
Section: Other Possible Effects Of Tankyrase Inhibition and Conclumentioning
confidence: 99%
“…6,7 Although the full extent of this protein's actions are still being discovered, mouse models have shown that this protein attaches to the tyrosine kinase c-abl, leading to an upregulation of inflammation and osteoclastogenesis. [8][9][10] Imatinib is an active inhibitor of the c-abl, c-kit, and platelet-derived growth factor tyrosine kinases. 4 Inhibiting c-abl could directly mitigate the effects of the aberrant 3BP2 protein.…”
Section: E5mentioning
confidence: 99%